A percepção de futuro acadêmico e profissional entre alunos plantonistas do programa “Plantão Psicológico”: o olhar sob o viés da fenomenologia-existencial - Souza, Caio Cesar Martins de (Brasil, 2024)
Training in Psychology recommends, among other factors, the insertion of the student in projects and extension programs with communities. Psychological duty in schools in the public education system has been a field of activity for students from various psychology courses in the city of Manaus. One of the issues present in this extension experience concerns the look at the student's being-himself considering the pluridimensionality of the experience. The objective of this study was to understand the perception of academic and professional future among students of Psychology courses at colleges in Manaus. The research is qualitative and the phenomenological research method in Psychology was used. The research instrument was the phenomenological interview that started from a guiding question that presented developments. The analysis of the interviews was carried out using the phenomenological-psychological method and subjected to the scrutiny of Heideggerian hermeneutics. The following categories were identified: a) A look at my history at university: senses and dissent; b) Entering the psychological shift and revealing myself, to the other, to Psychology; c) And the Clínica dos Três Olhares allows me to understand the phenomenality of the experience; d) Psychological shift and new perspective on the professional future: becoming becomes a clearing. It appears that working on psychological duty in public schools enabled participants to resize their views on their own path and find themselves as a being-in-the-world with possibility.